Northern getaway : film, tourism, and the Canadian vacation - Brégent-Heald, Dominique, 1973- (McGill-Queen's University Press, 2022)
"For more than a century, posters, advertisements, and brochures have characterized Canada as a desirable tourist destination offering spectacular scenery, wild animals, outdoor recreation, and state-of-the-art accommodations. However, these explicitly commercial displays are not the only marketing tools at the country's disposal; beginning in the 1890s, film also played a role in selling Canada. In Northern Getaway Dominique Brégent-Heald investigates the connections between film and tourism during the first half of the twentieth century, exploring the economic, pedagogical, geopolitical, and socio-cultural contexts and aspirations of tourism films. From the first moving images of the 1890s through the end of the 1950s, a complex web of public and private stakeholders in Canadian tourism experimented, sometimes in collaboration with Hollywood, with a variety of film forms - 16 mm/35 mm, feature films/short subjects, fiction/nonfiction, professional/amateur filmmakers - to promote Canada. Spectators, particularly Americans, saw Canada as a tourism destination in front of screens in motion picture theatres, schools, and fairgrounds. Rooted in settler colonial representations that celebrate the nation's unspoiled but welcoming wilderness landscapes, these films also characterize Canada as a technologically and industrially advanced settler country. Using evidence from a wide range of archival sources and drawing from current scholarship in film history and tourism studies, Northern Getaway demonstrates that Canada was an innovator in using film to shape and project a recognizable destination brand."--